Optimising Production of Kojic Acid from Sago Fibre by Solid-State Fermentation Using Response Surface Methodology - Dayang Salwani, Binti Awang Adeni; Alvin Miai, Spencer Empading; Nurashikin, Binti Suhaili; Ahmad, Husaini; Kopli, Bin Bujang (Borneo Journal of Resource Science and Technology (BJRST), 2019)
Kojic acid is an organic acid that has manifold industrial applications mainly in cosmetics, food and medicine. This research aims to optimise the production of kojic acid from sago fibre using a locally isolated Aspergillus flavus strain under solid-state fermentation (SSF). Central Composite Design (CCD) of Response Surface Methodology (RSM) consisting of 5 factors and 5 levels were employed to determine the influence of culture conditions such as initial moisture content (50-90% (v/w)), inoculum density (5-35% (v/w)), urea concentration (0.5-3.5% (w/w)), mineral salts solution (5-35% (v/w)) and incubation time (9-21 days) on kojic acid production. The results showed that the data were best represented by a quadratic model where the significant factors for kojic acid production were identified as inoculum density and incubation time with their optimal values of 30% (v/w) and 18 days, respectively. The maximum production of kojic acid achieved in this study represented a 2-fold increase from that achieved in the non-optimised conditions. In summary, this work describes the optimisation of kojic acid production from sago fibre employing RSM. In addition, this research represents a further step towards developing a sustainable production of kojic acid employing an eco-friendly and low-cost indigenous feedstock.